Role of English Language in Present Scenario in India: The Significance of English Language in India's Multicultural Society (Journal of Advances and Scholarly Researches in Allied Education, 2019)
English is a widely spoken language in the current scenario. It is dubbed the common language, the modern era's. It is the language that is most often taught throughout the world as a second language. English is used in the contact system with the outside world in India. This is also used for interaction between states and intrastate. India has great ethnic and linguistic diversity, so we can see English as an important' bridge' language. With the rapid advancement of IT, Research, Biology, Irrigation, Education, Mass Communication, Computer and Operating Systems, a new tool for written and oral media in the field. English is used all over the world not out of any compulsion but because of the realization that it has certain advantages. Communication is a skill which involves systematic and continuous process of speaking, listening and understanding. Most people are born with the physical ability to talk, but we must learn to speak well and communicate effectively. Speaking, listening and our ability to understand verbal and nonverbal cues are the skills by observing other people and modeling our behavior on what we see and perceived. We are also taught some communication skills directly through education. By bringing those skills into practice and getting them evaluated.